15th term of the sequence x - 7, x - 2, x + 3,... is
Answers
Answered by
11
Answer :
The Arithmetic sequence is
(x - 7), (x - 2), (x + 3), ...
The first term is
a1 = (x - 7)
and
the common difference is
d = (x - 2) - (x - 7)
= x - 2 - x + 7
= 5
So, the 15th term (n = 15) of the given Arithmetic sequence is
a15
= a1 + (n - 1)d
= (x - 7) + (15 - 1) × 5
= x - 7 + 14 × 5
= x - 7 + 70
= x + 63
#MarkAsBrainliest
The Arithmetic sequence is
(x - 7), (x - 2), (x + 3), ...
The first term is
a1 = (x - 7)
and
the common difference is
d = (x - 2) - (x - 7)
= x - 2 - x + 7
= 5
So, the 15th term (n = 15) of the given Arithmetic sequence is
a15
= a1 + (n - 1)d
= (x - 7) + (15 - 1) × 5
= x - 7 + 14 × 5
= x - 7 + 70
= x + 63
#MarkAsBrainliest
Answered by
4
Hi folka!!
Given :-
A.P. = (x - 7) , (x - 2) , (x + 3) ...
First Term [ a ] = x - 7
Common difference [ d ] =
- ![a_1 a_1](https://tex.z-dn.net/?f=a_1)
= (x - 2) - (x - 7)
= x - 2 - x + 7
= 7 - 2
= 5
Now,
term of the A.P. :-
= a + (n - 1) × d
= (x - 7) + (15 - 1) × 5
= (x - 7) + 14 × 5
= x - 7 + 70
= x + 63
Hence!!
15th term of A.P. (Sequence) = x + 63
Hope it helps uuuu ^_~
Given :-
A.P. = (x - 7) , (x - 2) , (x + 3) ...
First Term [ a ] = x - 7
Common difference [ d ] =
= (x - 2) - (x - 7)
= x - 2 - x + 7
= 7 - 2
= 5
Now,
= (x - 7) + (15 - 1) × 5
= (x - 7) + 14 × 5
= x - 7 + 70
= x + 63
Hence!!
15th term of A.P. (Sequence) = x + 63
Hope it helps uuuu ^_~
Similar questions